PENGARUH PENDAPATAN INVESTASI TERHADAP LABA PERUSAHAAN ASURANSI SYARIAH - Ikin Ainul Yakin; Irfan Hambali (UIN Sultan Maulana Hasanuddin Banten, 2019)
All insurance institutions would want to always experience an increase both in growth and maximum capital or profit increase. Profit or loss is usually used to assess the performance of the company's performance, the main factor in determining the size of the profits depends on the success of managing investments, where in 2018 investment income has dropped the company's profits have fallen. The formulation of the problems in this study are: 1). Is there an influence of investment income on the profits of the insurance company PT. Sinarmas Syariah ?. 2). How much influence does investment income have on the profits of the insurance company PT. Sinarmas Syariah? The purpose of this study are 1). To find out whether there is an influence of investment income on the profits of insurance companies PT. Sinarmas Syariah Insurance. 2). To find out how much influence the investment income on the profits of insurance companies PT. Sinarmas Syariah. This study uses simple linear regression analysis techniques Test statistics of classical assumption tests including normality test, heteroscedasticity test, and autocorrelation test and using hypothesis testing including two-sided t test, simple linear regression test and coefficient of determination test. Based on the results of the T test, the t value of investment income obtained 3.752 is greater than t table 2.0859 thus there is a significant influence on investment income on earnings. R2 value of 0.439 or (43.9%) which means the investment income variable influences profits by 43.9% while the remaining 56.1% is influenced by other factors not examined.